Q.2 - Hà, Minh Đức; Vũ, Tuấn Anh (H., 2001)
Giới thiệu truyện ngắn của nhiều tác giả: Khái Hưng, Thanh Châu, Thế Lữ, Lê Văn Trương, Hồ Hải Như Lang, Nguyễn Văn Nguyễn, Thạch Lam...
Keywords: Văn học Việt Nam -- Thế kỷ XX; Truyện ngắn Việt Nam -- Thế kỷ XX